2019
DOI: 10.1080/09637486.2019.1695758
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sociodemographic factors on eating motivations – modelling through artificial neural networks (ANN)

Abstract: This study aimed at investigating the influence of some sociodemographic factors on the eating motivations. A longitudinal study was carried conducted with 11960 participants from 16 countries. Data analysis included t-test for independent samples or ANOVA, and neural network models were also created, to relate the input and output variables. Results showed that factors like age, marital status, country, living environment, level of education or professional area significantly influenced all of the studied typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
2
6
1
Order By: Relevance
“…The present study confirms the results of previous studies, which found that the health motivations was one of the most important motivation among adults from different populations [26][27][28]. The results also confirm that health motivations for food choices predominate among urban adults [28,29]. One of the assumptions for this finding is that the nearly equal distribution of men and women, and people of all ages in this study may reduce the demographic influence on food choice motivations [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study confirms the results of previous studies, which found that the health motivations was one of the most important motivation among adults from different populations [26][27][28]. The results also confirm that health motivations for food choices predominate among urban adults [28,29]. One of the assumptions for this finding is that the nearly equal distribution of men and women, and people of all ages in this study may reduce the demographic influence on food choice motivations [29].…”
Section: Discussionsupporting
confidence: 91%
“…The results also confirm that health motivations for food choices predominate among urban adults [28,29]. One of the assumptions for this finding is that the nearly equal distribution of men and women, and people of all ages in this study may reduce the demographic influence on food choice motivations [29]. Second, almost one third of the participants had one of the chronic non-communicable diseases, 33.9% were overweight, and 11.6% were obese, which could increase the health motivations for food choices [26].…”
Section: Discussionsupporting
confidence: 68%
“…The questionnaire was developed as a part of the multinational project entitled "Psycho-social motivations associated with food choices and eating practices (EATMOT)". The design of the questionnaire was described in detail in previous works from the project team [24][25][26]. The questionnaire included two parts.…”
Section: Questionnairementioning
confidence: 99%
“…As part of a study in 16 countries that investigated psychological and social motivations that influence people's eating patterns (Guiné et al, 2019), Table 4 presents an extract of the results for Serbia related to eating sweet products (data not published). It is obvious that Serbian population disagrees that we should not eat sweet products and they understand that some people have cravings for sweets.…”
Section: Resultsmentioning
confidence: 99%